Factors associated with medication non-adherence among patients with severe mental disorder - A cross sectional study in a tertiary care centre - Papiya Ghosh; Sivaprakash Balasundaram; Avudaiappan Sankaran; Vigneshvar Chandrasekaran; Sukanto Sarkar; Sunayana Choudhury (Elsevier, 2022)
Background: Medications are an essential treatment modality of mental disorders. There is limited scientific literature on medication non-adherence among patients in Severe Mental Disorders with respect to patient-related factors. The current study explores the factors associated with medication non-adherence in such patients. Objectives: To study the relationship between socio-demographic, clinical, treatment related factors, self-stigma, patients' & caregivers' attitude towards psychotropic medications, doctor-patient communication and medication non-adherence in patients with severe mental disorders. Methods: A cross-sectional observation study, where patients with severe mental disorders attending Psychiatry Outpatient services, and their caregivers, were recruited. Sociodemographic and clinical variables were recorded using data collection form and illness-specific severity scales. Patients were administered Medication adherence rating scale (MARS), Internalised stigma of mental illness inventory (ISMI- 9), Attitude of patients towards psychotropic medication scale and Doctor-patient communication questionnaire (DPCQ). The Attitude of caregivers towards psychotropic medication scale was administered for caregivers. Results: Among 152 patients, 58 (38.16%) patients had a diagnosis of schizophrenia, 11 (7.24%) had delusional disorder, 32 (21.05%) patients were diagnosed with bipolar disorder type 1 - mania and 19 (12.50) with bipolar disorder type 2 - depression whereas 32 (21.05%) had major depressive disorder. Majority of the patients were non-adherent to medications (88.16%). MARS score was significantly higher among patients of middle socioeconomic class (p = 0.014), urban domicile (p = 0.033) and those with higher caregivers' age (p = 0.019) . Among 79.61% of patients, ISMI-9 score was minimal to mild. Most patients (76.97%) and caregivers (83.55%) had negative attitude towards psychotropic medications. MARS score negatively correlated with BPRS (p = 0.0001*), HAM-D (p = 0.0004*), YMRS (p = 0.0007*), ISMI-9 (p ≤0.0001*) and the attitude of the caregivers towards psychotropic medicationsnegative scale scores (p = 0.003*) . MARS score positively correlated with DPCQ scores (p ≤0.0001*) . Conclusion: Medication adherence was higher among patients belonging to uppermiddle socioeconomic status, urban domicile and higher caregiver age. Higher severity of illness, self-stigma and negative attitude of patients and caregivers towards psychotropic medications were associated with lower adherence whereas better doctor-patient communication was associated with higher adherence to medications.